1986
DOI: 10.1093/carcin/7.9.1415
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in diethylstilbestrol-induced mutagenicity and cell transformation by exogenous metabolic activation

Abstract: It was shown previously that diethylstilbestrol (DES) can induce morphological and neoplastic transformation of Syrian hamster embryo cells in culture in the absence of detectable gene mutations or DNA damage. However, in the presence of exogenous metabolic activation with rat liver post-mitochondrial supernatant, DES can induce unscheduled DNA synthesis. In this report we have examined whether with exogenous metabolic activation DES can also induce biological effects possibly related to its carcinogenicity, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…However, treatment of SHE cells with DES in the presence of an exogenous metabolic activation system enhances the frequency of morphological transformation of the cells. Furthermore, this treatment elicits UDS and gene mutations in the cells at the Na+/K+-ATPase locus (33). Thus, we have proposed two potential mechanisms for estrogen-induced cell transformation; in one the target of the estrogen is not DNA but rather microtubule disruption and the other is associated with DNA damage (33).…”
Section: Genotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, treatment of SHE cells with DES in the presence of an exogenous metabolic activation system enhances the frequency of morphological transformation of the cells. Furthermore, this treatment elicits UDS and gene mutations in the cells at the Na+/K+-ATPase locus (33). Thus, we have proposed two potential mechanisms for estrogen-induced cell transformation; in one the target of the estrogen is not DNA but rather microtubule disruption and the other is associated with DNA damage (33).…”
Section: Genotoxicitymentioning
confidence: 99%
“…Although DES is not genotoxic in many assays, in certain studies DES has been found to induce UDS (21,(70)(71)(72), sister chromatid exchanges (73)(74)(75), chromosome aberrations (76,77) and gene mutations (33,78). The positive studies of DNA damage by DES use either cultured mammalian cells with exogenous metabolic activation or cells with possible endogenous activation capacity for DES.…”
Section: Genotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…If there was displacement, they were scored as breaks. In some experiments, the chromosome aberration assay was carried out in the presence of exogenous metabolic activation with rat liver post-mitochondrial supernatant (PMS), as described previously (4). Cells (5´10…”
mentioning
confidence: 99%
“…This treatment condition is optimal for inducing gene mutations in SHE cells treated with indirectly acting chemical carcinogens (4). Cells were washed twice with 5 ml PBS(-) and incubated with fresh medium for 18 h followed by chromosome preparations.…”
mentioning
confidence: 99%